Multi-Exergames to Set Targets and Supplement the Intensified Conventional Balance Training in Patients With Stroke: A Randomized Pilot Trial - Cikajlo, Imre; Rudolf, Marko; Mainetti, Renato; Borghese, Nunzio Alberto (Frontiers in Psychology, 2020)
People who survive a stroke usually suffer movement disorders resulting in involuntary abnormal movements. Intensive and repetitive physiotherapy is often a key to functional restoration of movements. Rehabilitation centers have recently offered balance training supported by exergames in addition to conventional therapy. The primary objective was to investigate different types of balance training (multi-exergaming and conventional) in addition to a conventional 6-week physiotherapy program. Furthermore, we examined the choice of an appropriate exergame to target balance training. We designed a randomized pilot trial. Hospital inpatients with stroke aged 33 - 65 were recruited and randomized into 2 groups by drawing lots; a control group receiving 1 week of conventional balance training and an exergaming group 1 week of multiple-game exergaming, comprising single leg exercises, weight shifting, balancing and standing up. Center of pressure was monitored for the exergaming group and clinical data were collected (non-blinded assessment) using Four Square Step Test, Timed Up&Go, 10m Walk Test, Romberg, Sharpened Romberg, Clinical Test for Sensory Interaction in Balance in both groups. Statistical tests were used to find significant (p < 0.05) differences and Cohen’s U3 for effect sizes. Recruited participants (20 / 30) met the inclusion criteria and were randomized; 10 per group. 1 participant of the exergaming group was excluded from center of pressure analysis. Both groups demonstrated substantively and statistically significant improvements of functional balance, in particular the exergaming group (FSST p = 0.009, U3 = 0.9 and 10MWT p = 0.008, U3 = 0.9). However, significant differences between the groups were found in tests with eyes closed, Sharpened Romberg test (p = 0.05) and standing on the right leg (p = 0.035). The center of pressure area decreased up to 20% for the exergaming group. Both types of additional balance training demonstrated comparable outcomes, however the multi-exergaming could target specific motor control disorders by the selection of exergames according to Gentile's taxonomy. We may not prioritize exergaming due to the low statistical power of clinical outcomes. However, exergaming enables independent balance training, which is feasible without strenuous physiotherapy and may thus be crucial for future home or telerehabilitation services.